Beyond collective agreements: The rise of the wage cushion in Germany - André Rieder; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2025)
Representative establishment data reveal that over 60% of German plants covered by collective agreements pay wages above the level stipulated in the agree- ments, creating a wage cushion between actual and contractual wages. While collective bargaining coverage has fallen over time, the prevalence of wage cushions has increased, particularly in eastern Germany. Cross-sectional and fixed-effects analyses for 2008-2023 indicate that in western Germany the presence of a wage cushion is mainly related to plant profitability, unemployment, vacancies, and the business cycle. Plants which apply collective agreements at the firm rather than the sectoral level are less likely to have wage cushions since firm-level agreements make it easier to explicitly take firm-specific conditions into account. In eastern Germany, however, the explanatory power of these variables is much lower. Against the backdrop of falling bargaining coverage, the increasing prevalence of wage cushions suggests that the traditionally rigid German system of wage determination has become more flexible and differentiated. – – Repräsentative Betriebsdaten zeigen, dass über 60% der tarif- gebundenen Betriebe in Deutschland Löhne zahlen, die über dem in Tarifverträgen fest- gelegten Niveau liegen, wodurch ein Lohnpuffer zwischen den tatsächlichen und den vertraglich vereinbarten Löhnen entsteht. Während die Tarifbindung im Laufe der Zeit zurückgegangen ist, hat die Verbreitung der übertariflichen Entlohnung zugenommen, besonders in Ostdeutschland. Querschnitts- und Fixed-Effects-Analysen für 2008-2023 zeigen, dass in Westdeutschland das Vorhandensein eines Lohnpuffers hauptsächlich mit der Rentabilität des Betriebs, der Arbeitslosigkeit, offenen Stellen und dem Konjunk- turzyklus zusammenhängt. Betriebe, die Tarifverträge auf Betriebs- statt Branchen- ebene anwenden, zahlen seltener über Tarif, da es bei Firmentarifverträgen einfacher ist, betriebsspezifische Bedingungen ausdrücklich zu berücksichtigen. In Ostdeutsch- land ist der Erklärungswert dieser Variablen jedoch erheblich geringer. Vor dem Hinter- grund der sinkenden Tarifbindung deutet die zunehmende Verbreitung von Lohnpuffern darauf hin, dass das traditionell starre deutsche System der Lohnfindung flexibler und differenzierter geworden ist.
Keywords: J30; J31; 330; wage determination; collective bargaining; wage cushion; Germany